(untitled) (Journal of the College of Basic Education, 2026)
The current research aims to investigate the effect of the 4H strategy on critical reading skills among second-grade middle school students. chose a partially controlled experimental design. The research sample consisted of (63) students, with (31) students in the experimental group and (32) students in the control group. The two groups were matched on the variables of chronological age, parents’ academic achievement, intelligence test, and Arabic language scores. The researcher prepared study plans and a critical reading skills test, all of which were presented to experts, and validity and reliability were verified. At the end of the experiment, the researcher administered a critical reading skills test to measure these skills. The results showed that experimental outperformed in developing critical reading skills. Based on these findings, the researcher concluded that the 4H strategy is effective in teaching. Based on these findings, the researcher presented a number of recommendations and suggestions for conducting studies complementary to the current research.